Preparation and electrochemical investigation of the cobalt hydroxide carbonate/activated carbon nanocomposite for supercapacitor applications. (January 2016) - Masikhwa, Tshifhiwa M.; Dangbegnon, Julien K.; Bello, Abdulhakeem; Madito, Moshawe J.; Momodu, Damilola; Manyala, Ncholu
Abstract: Cobalt hydroxide carbonate/activated carbon (AC) composite was successfully synthesized by hydrothermal method. Morphological characterizations of cobalt hydroxide carbonate/AC composite were carried out by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the results show that the cobalt hydroxide carbonate nanorods are well dispersed on the AC. Due to the synergistic effects arising from cobalt hydroxide carbonate nanorods and AC, the electrochemical performances of pure cobalt hydroxide carbonate material is significantly improved by the addition of AC. The composite shows a specific capacitance of 301.44 F g −1 at a current density of 1 A g −1 in 6 M KOH electrolyte and exhibits good cycling stability. Based on the above results, the cobalt hydroxide carbonate/AC composite shows a considerable promise as electrode for electrochemical applications. Highlights: Hydrothermal synthesis of electrode materials . Cobalt hydroxide carbonate exhibited nanorods morphology. The composite exhibit improved electrochemical properties.